Application of Discovery Learning Based E-comic Media to Enhance Students' Visual Skills Literacy in History Subjects - Grey Ardia Anggraini; Jefri Rieski Triyanto; Alifi Nur Prasetia Nugroho (Universitas Pendidikan Ganesha, 2026)
This study was motivated by the low level of students’ visual literacy skills and the continued use of conventional history learning media in schools. The study aims to examine the influence and effectiveness of discovery learning-based e-comic media in improving students’ visual literacy skills in history learning. This research employed a quantitative approach with a quasi-experimental design involving two vocational high school classes with a total of 72 students. The experimental group used e-comic media, while the control group used e-books. Data were collected through pre-tests, posttests, and student interviews. Data analysis was conducted using the Independent Sample T-Test with the assistance of SPSS, while interview data were analyzed using NVIVO. The results showed a significant difference in visual literacy skills between the experimental group and the control group, with a large effect size. Interview findings also indicated that the use of e-comics increased students’ cognitive, compositional, and affective engagement in learning. The implications of this study suggest that the use of e-comic media can serve as an innovative alternative for teachers in developing more interactive history learning and supporting the improvement of students’ visual literacy skills. Therefore, discovery learning-based e-comic media has been proven effective in enhancing students’ visual literacy skills in history learning.